THE PROBLEMATIC LESSON IS ITS MEANING AND ESSENCE - Abdalova Sayyora Rustamovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the problem lesson, its goals and objectives, as well as its content and essence, the role of learners in the formation and development of learning competencies